Selected speeches 1984-87 R. Venkataraman: 10 September 1984- 14 May 1987 - Publications Division (New Delhi Publications Division, Ministry of Information and Broadcasting, GOI, 1991)
This is the first volume of the speeches of Shri R. Venkataraman as Vice-President, covering the period 10 September 1984 to 14 May 1987.These speeches outline his percep- tions of the nation's priorities, impera- tives and goals. They bring to bear on a variety of themes, the accumulated ex- perience of Shri Venkataraman's partici- pation in India's public life which commenced in the early 1930s.
Keywords: R. Venkataraman; Vice-President of India; President of India